2020
DOI: 10.1158/1078-0432.ccr-19-2891
|View full text |Cite
|
Sign up to set email alerts
|

The Nanocind Signature Is an Independent Prognosticator of Recurrence and Death in Uterine Leiomyosarcomas

Abstract: Purpose: Uterine leiomyosarcoma, which accounts for 7% of all soft-tissue sarcomas and 1%-3% of all uterine malignancies, is an aggressive tumor responsible for a significant proportion of uterine cancer-related deaths. While Federation Internationale des Gynaecologistes et Obstetristes (FIGO) stage is the most important prognostic factor, metastatic and relapse rates at stage I exceed 50% so it is currently impossible to predict the clinical outcome of stage I leiomyosarcomas. In 2010, our team published a tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A recent study on uterine sarcomas was performed, showing that potentially actionable mutations were identified in nearly half of the analyzed patients, even if the study confirmed the recurrent mutational profile of uLMS dictated by TP53 , RB1 and ATRX genetic hits [ 19 ]. Even if novel genetic signatures are discovered and proposed to stratify patients with respect to prognosis [ 20 ], their impact on the clinical management of patients or on the development of novel therapeutic opportunities is still marginal.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on uterine sarcomas was performed, showing that potentially actionable mutations were identified in nearly half of the analyzed patients, even if the study confirmed the recurrent mutational profile of uLMS dictated by TP53 , RB1 and ATRX genetic hits [ 19 ]. Even if novel genetic signatures are discovered and proposed to stratify patients with respect to prognosis [ 20 ], their impact on the clinical management of patients or on the development of novel therapeutic opportunities is still marginal.…”
Section: Introductionmentioning
confidence: 99%
“…The signature demonstrated its prognostic value in a series of 60 ULMS by identifying a group of patients with low risk of recurrence and death with a 5‐year RFS of 51% and a 5‐year OS of 86% vs a 5‐year RFS of 9% and 5‐year OS 29% for the high‐risk group (Figure 3A,B) (RFS: P = 6.7×10 −4 , HR = 3.71) (OS: P = 7.56×10 −4 , HR = 5.97). Thus, in multivariate analysis, it outperformed the GI at the threshold of 35, which was prognostic for OS but not for RFS 60 …”
Section: Genomic Complexity and Uterine Smooth Muscle Tumorsmentioning
confidence: 92%
“…The pertinence of the CINSARC signature in ULMS was demonstrated in stage 1 ULMS with 5‐year OS of 84% and 5‐year RFS of 59% for the low‐risk group vs 39% of 5‐year OS and 15% 5‐year RFS for the high‐risk group (OS P = 9.89×10 −3 ; HR = 5.51) (RFS P = 3.38×10 −3 ; HR = 3.83). Again, in multivariate analysis, it outperformed the GI at the cutoff of 35 and atypia 60 (Figure 4A‐C). These results were validated in an independent cohort (32 ULMS) from TCGA 51 .…”
Section: Genomic Complexity and Uterine Smooth Muscle Tumorsmentioning
confidence: 95%
“…FIGO staging remains the primary prognostic factor, alongside an uLMSspecific nomogram for predicting post-resection 5-year OS 39,40 . There is a need for improved prognosticators to identify patients who might benefit from adjuvant chemotherapy 41 . Italiano et al showed that CINSARC classified 73 primary LMS, of multiple anatomical locations, into two groups with significantly different MFS 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Italiano et al showed that CINSARC classified 73 primary LMS, of multiple anatomical locations, into two groups with significantly different MFS 42 . In a retrospective series of 60 uLMS CINSARC divided this cohort, of all FIGO stages, into high-risk (C2) and low-risk (C1) groups 41 . C2 had 5-year relapse-free survival (RFS) rate of 9% compared to 51% in C1.…”
Section: Introductionmentioning
confidence: 99%